Hydrogen Embrittlement of Galvanized Press-Hardened Steels: A Review - Tomáš Kročil; Nikola Macháčková; Tomáš Prošek; Thomas Steck; Reza Sharif (Metals)
Press-hardened steels (PHS), as an alternative to traditional steels and aluminum alloys, combine great mechanical performance with low manufacturing costs. PHS are martensitic steels with ultimate tensile strength (UTS) up to 2000 MPa. These steels are commonly coated with zinc-based coatings (PHS GI) consisting of multiple Zn–Fe phases to enhance corrosion resistance. However, similar to all high-strength steels, PHS are known for their elevated susceptibility to hydrogen embrittlement (HE). Absorption of atomic hydrogen into the steel lattice can lead to a transition from a ductile to a brittle fracture mechanism and decrease the stress necessary for fracture initiation. This review examines the microstructure of PHS GI with a focus on how the manufacturing process influences key parameters of the coating. The material’s susceptibility to HE is discussed in the following sections, along with the potential for hydrogen introduction through corrosion in atmospheric environments. The relationship between the content of hydrogen and its effects on fracture behavior is discussed, along with the corrosion behavior of PHS GI. The potential areas for future research and development of PHS GI with increased HE resistance are proposed.